Shifting the focus from gender diversity and inclusion to belonging and gender equity in Aotearoa New Zealand community football organisations : how did we get here and where are we going? : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Manawatū, Aotearoa New Zealand - Shanks, Alida (Massey University, 2023)
Gender equity in community football organisations remains elusive despite national and international moves to address this through legislation, reports, and strategies focusing on gender diversity and inclusion. This research demonstrates that we are in the position we are today because in their attempts to promote gender equity, national sports organisations and Sport NZ (in its current and previous incarnations) have essentially placed all their emphasis on devising and implementing policy. This approach has produced, at best, symbolic equality. While we have seen some progress in this space, there is much more to do for a sustained change in attitudes and behaviour towards gender diversity and inclusion to achieve gender equity within community sports organisations. Historically, this research shows that legislation and policies are a fairly blunt instrument for changing behaviour, because while they are important statements of what governments and organisations believe, this has not translated into practice. This research provides a historical analysis of this issue, by tracing the history of women’s involvement in community football organisations in Aotearoa NZ within the wider context of women’s involvement in sports organisations, and with reference to the scholarly literature on the history of women’s sport. It discusses the academic literature on gender diversity and inclusion in sport at micro-, meso-, and macro-levels, and draws on analyses of previous frameworks to conceptualise and create a new model, the Belonging and Equity Model. I adopted a relativist ontological approach, a social constructionist epistemology, underpinned by post-structural feminism. Taking a holistic approach, I used a multi-disciplinary methodology, mixed data collection methods and multiple sources of evidence that focused on converting theories and research into practicable tools for community football organisations to use. I applied a qualitative approach, using case study and insider research that included historical context, a web-based survey, action research, and a human-centred design thinking workshop to pilot and review the Belonging and Equity Model, a theoretical framework which was refined and evolved to become the practical Te Poukapa: The Belonging and Equity Matrix. The findings showed that there is a lack of diversity in community football organisations and more than a third of women who work in regional football federations have experienced discrimination. What is needed are actions that focus on belonging and gender equity, including at a strategic level, knowing and owning our (her)story, introducing gender equitable rituals, and building trust at all levels. This research discusses both the reasons for how we got ‘here’ and offers recommendations on how to move forward.
Keywords: Soccer; Community organization; Management; Sex discrimination in sports; New Zealand; 350711 Organisational planning and management; 440509 Women's studies (incl. girls' studies)